Analysis Of The Relationship Between Nutritional Status And Length Of Work On Fatigue In PT. X - Sunaryo, Merry; Hutapea, Octavianus; Ayu, Friska (Universitas Nahdlatul Ulama Surabaya, 2022)
Protection from work accidents and occupational diseases is what occupational health and safety refers to for employees who are valued assets for enterprises. If this disease is not appropriately treated, symptoms such as work tiredness, which has numerous potential causes, may manifest. In order to prevent worker weariness, it is crucial to understand the causes of it. In this work, cross sectional observational research with quantitative approaches is used. The study's population consisted of PT. Y employees, with a sample size of 45 individuals. The findings of this study suggest that a number of factors influence worker weariness at work. According to the investigation, the length of the workday and nutritional status are the main contributors to fatigue at PT. Y. It is evident from the significance value's results, which have a value less then 0.05. according to the value is the connection between nutritional status and the occurrence of fatigue, it is known that it has a p-value of <0.005, which is 0.000. Then on the results of the analysis of the length of work with fatigue it is known that the p-value <0.005, which is 0.015. Therefore, it can be said that variables contributing to the onset of weariness include nutritional state and the length of work. Therefore, changes must be made to prevent or lower the incidence of worker weariness, such as implementing